Power Plants in the Industry - Taner, Tolga (IntechOpen, 2019)
The main aim of this study is to present power plants for all fields of industry. The chapters collected in the book are contributions by invited researchers with long-standing experience in different research areas. I hope that the material presented here is understandable to a wide audience, not only energy and mechanical engineering specialists but also scientists from various disciplines. The book contains seven chapters in two sections: (1) "Power Plants & Technical Details" and (2) "Power Plants in Different Fuels". This book shows detailed and up-to-date evaluations in different areas and was written by academics with experience in their field. It is anticipated that this book will make a scientific contribution to power plant workers, researchers, academics, MSc and PhD students, and other scientists in both the present and future.